A MONOGRAPHIC REVISION OF THE GENUS PODOCARPUS (PODOCARPACEAE): II. THE SPECIES OF THE CARIBBEAN BIOREGION* - Mill, R. R. (Edinburgh Journal of Botany, 2015)
The species of Podocarpus L’Hér. ex Pers. (Podocarpaceae) occurring on the islands of the Caribbean (excluding Trinidad and Tobago) are revised. Nine species are recognised, of which eight are known to be endemic to the Caribbean Bioregion. None of the species have infraspecific taxa. Four occur on Cuba, two on Hispaniola, two on Jamaica, and one on Puerto Rico and the Lesser Antilles. Keys are provided to all the species and to the species of Cuba, Hispaniola and Jamaica. The distributions of all species are mapped and discussed in relation to the geological history of the region as well as the climate, especially rainfall. The names Podocarpus urbanii Pilg. and Podocarpus buchii var. latifolius Florin are lectotypified. Revised or new IUCN conservation assessments are proposed for Podocarpus angustifolius, P. aristulatus and P. victorinianus and the existing assessments are detailed for the remaining species.